Sustained censorship in IT (2026-06) (Italy) - Voidly (2026)
CRITICAL severity censorship detected in Italy. Confidence: 85%. Data sourced from OONI.
Censorship Incident ID: IT-2026-0028
Keywords: censorship; IT; censorship; critical